“It’s just common sense”: How the (re)production of nostalgia sustains the sex binary and perpetuates oppression in U.S. politics and culture - Awak-Essien, Andrew-Jay (2021)
Discourse within transgender studies concerning anti-transgender rhetoric is often preoccupied with the removal and denial of transgender rights. The existing literature pays significantly less attention to the role of nostalgia in (re)producing the sex and gender binary which serves as the foundation for anti-transgender violence both on a structural and interpersonal level. An analysis of how seeds of nostalgia are sown and fertilised within society through law, architectural and technological design, and feminist discourse helps us understand how the ideology that sex is binary and immutable is ostensibly neutralised through its presentation as ‘common sense’ and ‘natural order’. This dissertation is organised into three parts. Chapter One explores how definitions of biological sex have historically been and are currently being contested in U.S. law. The chapter examines how the Trump administration’s deliberate denial of sex variation and its complexities, and their depiction of transgender people as economically taxing to America, presents the solidification of the sex binary as a part of making America great again. Through the infamous ‘bathroom debates’ Chapter Two examines how as a result of people’s sense of identity being challenged alongside the sex binary, people cling on to material sites as indicators of a ‘past’ stability and permanence. How design is used as a tool of capitalism to cement the sex binary within Western culture, and the subsequent proliferation of anxieties and policing that has arisen as transgender people seek to relieve themselves is illustrated. Chapter Three explains how despite the argument put forward by trans-exclusionary radical feminists that binary biological sex difference is fundamental to womanhood, this is not the case. The desire to deny women the status of womanhood on a biological basis is not new, but has been (and is still) used to deny Black women, transgender women and intersex women womanhood. Therefore this dissertation scrutinises the ideology that biological sex is binary and immutable. It highlights how this binary is (re)produced and (re)constructed through nostalgia, and emphasises that any thought that does not work towards deconstructing the sex binary will ultimately (re)produce gendered, racist and patriarchal oppression.